Understanding beliefs and preferences of irrigators towards the use and management of agricultural water in the Colorado River Basin - Kallenberger, Julie A., author; Bright, Alan, advisor; Knight, Rick, committee member; Pritchett, James, committee member (Colorado State University. Libraries, 2013)
The agriculture sector in the American West is faced with multiple challenges including urbanization, drought, an aging producer population, and the prospects of climate change. As a result, the availability, use, and allocation of water throughout the West have become sources of both conflict and collaboration. Growing conflict emphasizes the need to identify and understand the diversity of beliefs of agricultural water users. This in turn, will help stakeholders better manage limited water resources and identify solutions for agricultural producers to deal with uncertainty and the pressures they are experiencing. This study examines the findings from a survey of farmers and ranchers who use Colorado River water for agricultural purposes, including: the pressures they are experiencing on their water supplies, options for addressing pressures, their interest and involvement in water transfer arrangements, and their preferences for meeting future water demands. In addition, their beliefs towards water availability, the role of storage, water policy and law, and working together with other stakeholders to address water challenges will be discussed. In brief, the results of this study indicate that agricultural water users face myriad number of pressures on their water supplies with drought and urban growth topping the list. The data indicates strong opposition towards agricultural water transfers, even those of temporary nature due to the concern of possibly losing their water right. A majority of participants agree that there will not be enough water for agriculture in their area or in the Colorado River Basin and that further water storage is needed to address uncertainty; however, new storage projects should be expanded before initiating new projects. Overall, agricultural water users agree that they need to partner with other non-agricultural water users (preferably at the district or basin level) in order to address the challenges they face or will face in the future. Multiple types of water stakeholders can benefit from the information found in this study by learning the differences, commonalities, viewpoints, and preferences of the agricultural sector and by using it to help gauge support for or against management decisions and policies, help predict and mitigate conflict among competing users, and to help develop approaches for working together collaboratively to address water issues in the Colorado River Basin.
Keywords: Colorado River; water transfer; water; irrigation; agriculture; cognitive hierarchy model of human behavior